The Latin Language and Medical Terminology. Human Anatomy : Training Manual for Self-Study for the First-Year Students of the Medical Faculties with the English Medium of Instruction - Тітієвська, Тетяна Василівна; Світлицький, Андрій Олександрович; Гордієнко, Олена В'ячеславівна; Куліченко, Алла Костянтинівна; Пашко, Олексій Єфремович (Запорізький державний медичний університет, 2019)
A training manual for self-study is made up for the first-year students of the medical faculties with the English medium of instruction (Specialty 222 “General Medicine”). All teaching materials are selected in accordance with the international anatomical and histological nomenclature and agreed with the Department of Human Anatomy, Operative Surgery and Topographic Anatomy of ZSMU.
Латинська мова та медична термінологія. Анатомія людини : навч. посіб. для самост. роботи студ.-іноз. гром. І курсу мед. ф-тів (спец. 222 “Медицина”)